Research considerations in the evaluation of minimally invasive pancreatic resection (MIPR). Issue 3 (March 2017) - ; Asbun, Horacio J.; Barkun, Jeffrey; Besselink, Marc G.H.; Boggi, Ugo; Conlon, Kevin C.P.; Han, Ho-Seong; Hansen, Paul D.; Kendrick, Michael L.; Kooby, David A.; Montagnini, Andre L.; Palanivelu, C.; et al.
Abstract: The IHPBA/AHPBA-sponsored 2016 minimally invasive pancreatic resection (MIPR) conference held on April 20th, 2016 included a session designed to evaluate what would be the most appropriate scientific contribution to help define the increasing role of MIPR internationally. Participants in the conference reviewed the assessment of numerous pertinent scientific designs including randomized controlled trial (RCT), pragmatic international RCT, registry-RCT, non-RCT with propensity matching, and various types of clinical registries including those aiming to create a quality improvement data system or a learning health care system. The strengths and weaknesses of each of these designs, the status of trials which are currently recruiting patients, and pragmatic considerations were evaluated. A recommendation was made to establish a clinical registry to collect data prospectively from around the world to assess current practices and provide a framework for future studies in MIPR.